2008
DOI: 10.1007/s10508-008-9420-3
|View full text |Cite
|
Sign up to set email alerts
|

Societal Individualism Predicts Prevalence of Nonhomosexual Orientation in Male-to-Female Transsexualism

Abstract: There are two distinct subtypes of male-to-female (MtF) transsexuals: homosexual and nonhomosexual. The relative prevalence of these two subtypes varies dramatically between countries, but no explanation of this variability has yet been proposed. This study examined the hypothesis that the prevalence of nonhomosexual MtF transsexualism, relative to homosexual MtF transsexualism, would be higher in individualistic countries than in collectivistic countries. I analyzed data from 22 studies of MtF transsexualism,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
27
0
2

Year Published

2009
2009
2022
2022

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 38 publications
(29 citation statements)
references
References 46 publications
0
27
0
2
Order By: Relevance
“…Third, Blanchard and others have stressed the importance of distinguishing between homosexual and non-homosexual transsexuals, suggesting that each group has a possibly separate etiology (Blanchard & Sheridan, 1992). Since previous research in a Spanish population found high proportions of MF (89.9%) and FM (94.4%) transsexuals reporting same-sex sexual orientation (Gómez-Gil et al, 2009) compared with previous European studies (Lawrence, 2008), we did not consider that the lack of a separate analysis of sexual orientation would change our findings. Finally, the total number of biological siblings of the probands was estimated from the real number of siblings in a subsample of probands, which did not include those with a transsexual sibling.…”
Section: Discussionmentioning
confidence: 66%
“…Third, Blanchard and others have stressed the importance of distinguishing between homosexual and non-homosexual transsexuals, suggesting that each group has a possibly separate etiology (Blanchard & Sheridan, 1992). Since previous research in a Spanish population found high proportions of MF (89.9%) and FM (94.4%) transsexuals reporting same-sex sexual orientation (Gómez-Gil et al, 2009) compared with previous European studies (Lawrence, 2008), we did not consider that the lack of a separate analysis of sexual orientation would change our findings. Finally, the total number of biological siblings of the probands was estimated from the real number of siblings in a subsample of probands, which did not include those with a transsexual sibling.…”
Section: Discussionmentioning
confidence: 66%
“…MtF transsexuals in most Western countries are predominantly nonhomosexual (Lawrence, 2008c), so it is especially important to consider the extent to which nonhomosexual MtF transsexuals constitute a homogeneous group. In most respects, this appears to be the case: Nonhomosexual MtF transsexuals who are attracted to women, to women and men, and to neither women nor men do not differ significantly with respect to cross-gender fetishism (Blanchard, 1985), childhood cross-gender behavior (Blanchard, 1988), age of clinical presentation (Blanchard, 1988), or autogynephilic sexual arousal (Blanchard, 1989b; see also Lawrence, 2005).…”
Section: Typologies Based On Sexual Orientationmentioning
confidence: 99%
“…As such, they are more likely to be overtly feminine during childhood and adolescence and are therefore more likely to experience the gender-based MtF male-to-female transsexual, FtM female-to-male transsexual, M mean, SD standard deviation, BDI Beck Depression Inventory, SCID II Structured Clinical Interview for DSM-IV Axis II Personality Questionnaire, SAD (total) Social Avoidance and Distress, SAD (AS) Social Avoidance and Distress, social anxiety scale, SAD (ES) Social Avoidance and Distress, social avoidance scale, FNE Fear of Negative Evaluation victimization and harassment and that may make them leave school or have difficulties in school. Lower social individualism has been associated with homosexual orientation in transsexuals and might explain these differences found between countries (Lawrence, 2010b). Regarding marital status, significant differences were found inthis population.Our resultsupportsliterature showingthatFtM transsexuals are more likely to live as couples and maintain more stable relationships than MtF transsexuals (De Cuypere et al, 1995;Dixen, Maddever, Van Maasdam, & Edwards, 1984;Gómez-Gil et al, 2009;Verschoor & Poortinga, 1988).…”
Section: Sociodemographic Characteristicsmentioning
confidence: 91%